2021
DOI: 10.52533/johs.2021.1701
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Low Back Pain Among Medical Students and Prolonged Unhealthy Sitting with E-learning During COVID-19 Pandemic

Abstract: Background: During the Covid-19 pandemic, Saudi Arabia instructed all institutions to deliver online educational activities. Distance e-learning emerged as an alternative to traditional education. E-learning involves long hours of sitting which can lead to postural problems and a series of health issues, including low back pain among medical students. This study is aimed to identify the correlation between low back pain and prolonged sitting during e-learning during the COVID-19 pandemic among medical students… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…This finding is in line with Eloi et al [ 24 ] who reported that 75.8% of students from all levels of a medicine program experience chronic pain that affects their positions and abilities to stand for an extended period of time. In a similar vein, El-Bidawy et al [ 20 ] reported that 60% of the sample reported that rest helped with pain relief.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…This finding is in line with Eloi et al [ 24 ] who reported that 75.8% of students from all levels of a medicine program experience chronic pain that affects their positions and abilities to stand for an extended period of time. In a similar vein, El-Bidawy et al [ 20 ] reported that 60% of the sample reported that rest helped with pain relief.…”
Section: Discussionmentioning
confidence: 92%
“…Half of the current study’s nursing students had normal body mass indexes. A previous study by El-Bidawy et al [ 20 ] on the medical college students at a Saudi university showed a positive correlation between being overweight and experiencing low back pain. They reported that the average body mass index of the medical student participants was 26.39 (±6.16).…”
Section: Discussionmentioning
confidence: 98%